sncRNAs packaged by Helicobacter pylori outer membrane vesicles attenuate IL-8 secretion in human cells - Hongxia Zhang; Yingxuan Zhang; Zifan Song; Ruizhen Li; Huan Ruan; Qiong Liu; Xiaotian Huang (Elsevier, 2020)
Bacterial outer membrane vesicles (OMVs) play a vital role in the mechanism of host-pathogen communication, while emerging evidence suggests that OMVs regulate host immune responses through differentially packaged small noncoding RNAs (sncRNAs) to target host mRNA function. Therefore, we identified differentially packaged sncRNAs in Helicobacter pylori OMVs and showed transfer of OMV sncRNAs to human gastric adenocarcinoma cells in this study. Our data revealed that sncRNAs (sR-2509025 and sR-989262) were enriched in OMVs, and reduced lipopolysaccharide or OMV-induced interleukin 8 (IL-8) secretion by cultured AGS cells. Collectively, these findings are consistent with the hypothesis that sncRNAs in H. pylori OMVs play a novel role in the mechanism of host-pathogen interaction, whereby H. pylori evades the host immune response.